2012
DOI: 10.7314/apjcp.2012.13.6.2429
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Isocyanate and Carcinogenesis: Bridgeable Gaps in Scientific Knowledge

Abstract: Methyl isocyanate may have a role in cancer etiology, although the link is unclear. There is evidence in the literature that it can induce cancer in animals but the carcinogenic potency is weak. Pheochromocytoma of adrenal medulla and acinar cell tumors of pancreas have been observed in methyl isocyanate exposed animals. Conversely, emerging data from population-based epidemiological studies are contradictory since there is no evidence of such cancers in methyl isocyanate exposed humans. Recently, we reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Besides, the immunotoxic (Karol et al, 1987), genotoxic (Conner et al, 1987;Tice et al, 1987), reproductive and developmental toxic effects (Schwetz et al, 1987) are well-documented in humans and animals. However, the etiology of MIC in carcinogenesis is far from completely understood (Senthilkumar et al, 2012;Senthilkumar, 2012). Data from animal studies have shown that the carcinogenic potency of MIC is low and weak (Gassert et al, 1986;Ennever and Rosenkranz, 1987;Bucher and Uraih, 1989).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the immunotoxic (Karol et al, 1987), genotoxic (Conner et al, 1987;Tice et al, 1987), reproductive and developmental toxic effects (Schwetz et al, 1987) are well-documented in humans and animals. However, the etiology of MIC in carcinogenesis is far from completely understood (Senthilkumar et al, 2012;Senthilkumar, 2012). Data from animal studies have shown that the carcinogenic potency of MIC is low and weak (Gassert et al, 1986;Ennever and Rosenkranz, 1987;Bucher and Uraih, 1989).…”
Section: Research Articlementioning
confidence: 99%
“…Evidence from in vitro studies suggest MIC-induced oncogenic transformation in human cells (Mishra et al, 2009abc;Raghuram et al, 2010;Hariom and Mishra, 2011;. But still, toxic chemical substances analyzing agencies are categorizing MIC as a non-carcinogenic substance (Senthilkumar et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…Undoubtedly, another group who should be in the debate is the life-threatening chemical exposed people surviving with chronic respiratory disorders. Here, we emphasize one such population who faced the World's worst chemical disaster in 1984 in Bhopal (Figure 1), survived the deadly methyl isocyanate (MIC) exposure with multiple complications including cancers [5][6][7] , pulmonary function abnormalities 8 , and obstructive lung function 9 . Almost thirty-five years over, the MIC-exposed long-term survivors and their offspring born post-exposure (also referred to as the Bhopal MIC-affected population) and their health status remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl isocyanate (MIC) is used for carbamylation of amines as an important precursor for the synthesis of carbamate pesticides and diisocyanates (i.e., intermediates in synthesis of plastics) (13). Although industrially important, MIC is also highly toxic, as tragically demonstrated by Bhopal disaster in 1984, where it is estimated that 8000 or more people died within minutes of exposure to MIC (46).…”
Section: Introductionmentioning
confidence: 99%